Judith Butler: A Foucaultian feminism? (Devenires, 2007)
In The will to knowledge Michel Foucault puts forward one of the most controversial thesis for some feminist groups, in which ‘sexuality’, far from being repressed, is produced by modern relations of power. This thesis was later retaken by the theoretical feminist Judith Buther, for whom sexuality is the same construct of power as it was for Foucault. However, to unveil all the working mechanisms of sexuality, it is necessary to insert it into a broader epistemic regime: the heterosexual matrix. Foucault talked about the constitution of subjects of desire, but did not say anything about their ‘heterosexualization’. It is in this moment that Butler decides to enter into the discourse that Foucault previously denounced: that of psychoanalysis. To what extent Butler’s feminism continues being Foucaultian? This is the question we want to answer in the text.
Keywords: Judith Butler; Foucault; feminism